Snooze or Lose: High School Start Times and Academic Achievement - Jeffrey A. Groen; Sabrina Wulff Pabilonia (Institute of Labor Economics (IZA), 2017)
Many U.S. high schools start classes before 8:00 A.M., yet research on circadian rhythms suggests that students' biological clocks shift to later in the day as they enter adolescence. Some school districts have moved to later start times for high schools based on the prospect that this would increase students' sleep and academic achievement. This paper examines the effect of high school start times on student learning. We use longitudinal data from the Child Development Supplement to the Panel Study of Income Dynamics (PSID-CDS) to conduct the first study of this relationship using a nationally-representative sample of students. We also use the CDS time diaries to explore the effects of high school start times on students' time allocation. Results indicate that female students who attend schools with later start times get more sleep and score higher on reading tests. Male students do not get more sleep when their schools start later and their test scores do not change.
Keywords: I12; I20; J22; 330; academic achievement; school start times; sleep; time allocation